Electrical Control Systems for the Future: Integration and Innovation of Digital Intelligent Technologies - Meng, Fanxu (International Journal of Mechanical and Electrical Engineering, 2025)
Electrical control systems are a key component of modern industry and daily life. From power generation to smart homes, from industrial automation to smart cities, electrical control systems are everywhere. With the continuous development of intelligent technology and digital transformation, electrical control systems play an increasingly important role in multiple industries. This paper analyzes the current status and future development trends of this field by exploring the integration and innovation of digital and intelligent technologies in electrical control systems. Combined with industry development cases, this paper proposes the future technical development direction of electrical control systems and explores the application of smart grids, industrial automation, and building energy management. Finally, the article evaluates the actual application effect of digital intelligent technology in electrical control systems and proposes the possibilities and challenges of future technological innovation.